"Cutting Editors Faster Than We're Cutting Reporters": Influences of The Athletic on Sports Journalism Quality and Standards. (June 2022) - Buzzelli, Nicholas R.; Gentile, Patrick; Sadri, Sean R.; Billings, Andrew C.
Since its 2016 launch, negative attitudes toward The Athletic, a network of hyperlocal subscription sports news sites, have resonated throughout the journalism community because of the new media startup's nontraditional approach, one centered on hiring established journalists from the hometown newspaper. Therefore, to accurately paint a picture of The Athletic 's perceived impact on print journalism, 22 in-depth interviews were conducted with newspaper sports editors. This analysis reveals that most sports editors were generally accepting of The Athletic and viewed its presence as reinforcement that newspapers need to stick to daily coverage to stand out in the crowded sports media marketplace.